Riding the Waves: Farmer Resilience in Peri-Urban Area of Malang City - Kusuma, Adhinugraha Wirayudha; Rozuli, Ahmad Imron (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2025)
Rapid urbanization in Malang City's peri-urban areas has reduced agricultural land and increased economic pressure on farmers, leading to a decline in active farmers. To cope with these challenges, farmers develop resilience strategies to sustain their livelihoods. However, research on peri-urban farmer resilience remains limited, particularly in linking cultural and economic dimensions to survival strategies. This study analyzes farmer resilience patterns in response to land use changes and urbanization pressures. A qualitative approach was employed, using in-depth interviews and participatory observation with five landowner farmers and one key informant, a village official in Kedungrejo Village, Malang Regency. Findings identify five key resilience strategies: (1) perception of land as sacred ancestral heritage, (2) family solidarity, (3) financial adaptation through productive debt systems, (4) job diversification, and (5) Application of the life philosophy of Nrimo Ing Pandum values. These strategies are linear and flexible, allowing farmers to transition between resilience forms as needed. Theoretically, this study expands agrarian resilience discourse by integrating coping, adaptive, and transformative capacities in a dynamic peri-urban context. Practically, it offers policy recommendations, including incentives for farmland preservation and livelihood diversification programs within the agricultural sector, ensuring social and ecological stability in peri-urban areas